2010
DOI: 10.4269/ajtmh.2010.09-0603
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis var. israelensis (Bti) Provides Residual Control of Aedes aegypti in Small Containers

Abstract: We examined the use of megadoses of VectoBac WG for residual control of Aedes aegypti in 2-L plastic buckets. Doses of 10×, 20×, and 50× the recommended rate of 8 mg/L provided ≥ 90% control for 8, 8, and 23 weeks, respectively. There was no significant difference in mortality between dry (neat) or aqueous mixture of VectoBac WG. Pretreatment of dry containers up to 8 weeks before flooding did not significantly decrease efficacy through 11 success weeks. Thus, megadoses of dry formulations of Bti can be used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 15 publications
0
32
0
7
Order By: Relevance
“…After misting, the test cups were left undisturbed for 30 minutes before being fitted with a lid and collected. They were placed in respective treatment crates covered with mosquito-proof mesh similar to that used by Ritchie and others (2010) and transported 17 to a shaded outdoor area that was exposed to rainfall. This placement enabled controlled conditions for rearing, thus, reducing the influence of random environmental effects to the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After misting, the test cups were left undisturbed for 30 minutes before being fitted with a lid and collected. They were placed in respective treatment crates covered with mosquito-proof mesh similar to that used by Ritchie and others (2010) and transported 17 to a shaded outdoor area that was exposed to rainfall. This placement enabled controlled conditions for rearing, thus, reducing the influence of random environmental effects to the study.…”
Section: Methodsmentioning
confidence: 99%
“…israelensis (Bti) is an established microbial agent that kills mosquito larvae when ingested. 17,18 It is target-specific, free from bacterial contaminants and exotoxins, safe for drinking water, and poses no significant hazards to the environment. 14,19 Furthermore, it is effective against dengue vectors in village, urban, and suburban environs, and it has recently been reported as reducing dengue cases and vector numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of larvicides to kill all immature stages during an outbreak remains an important issue. A study to increase the residual effect of Bti in small temporary containers is warranted and recommended (13). Furthermore, the dengue viruses persist in viremic patients during an outbreak; therefore, it is also critical to decrease the risk of female mosquitoes becoming infectious females by killing the pupae.…”
mentioning
confidence: 99%
“…israelensis residual activity in many different conditions, including rivers, lotic zones, benthic zones (1, 2, 39), saltmarshes (8), and water tanks and containers (6,34). It was shown that this residual activity ranged from a few days to several months, and many environmental factors (e.g., UV light, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%